2007
DOI: 10.1080/15287390600975137
|View full text |Cite
|
Sign up to set email alerts
|

Potential Ecological and Human Health Impacts of Antibiotics and Antibiotic-Resistant Bacteria from Wastewater Treatment Plants

Abstract: The occurrence of antibiotics and other pharmaceuticals in the environment has become an increasing public concern as recent environmental monitoring activities reveal the presence of a broad range of persistent pharmaceuticals in soil and water. Studies show that municipal wastewater treatment plants (WWTPs) are important point sources of antibiotics and antibiotic-resistant bacteria in the environment. The fate of antibiotics and other pharmaceuticals in WWTPs is greatly influenced by the design and operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
191
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(204 citation statements)
references
References 57 publications
2
191
0
11
Order By: Relevance
“…β-Lactam antibiotics have been detected in wastewater systems (Brown et al, 2006), although they are not persistent in aquatic environments due to hydrolysis of the β-lactam ring (Cha et al, 2006). Previous data have shown significantly higher numbers of antibiotic-resistant bacteria in wastewater compared to the natural environment (Kim and Aga, 2007). Little is currently known about the dynamics of antibiotic-resistant bacteria and genes encoding antibiotic resistance in wastewater treatment plants (WWTPs).…”
Section: Introductionmentioning
confidence: 99%
“…β-Lactam antibiotics have been detected in wastewater systems (Brown et al, 2006), although they are not persistent in aquatic environments due to hydrolysis of the β-lactam ring (Cha et al, 2006). Previous data have shown significantly higher numbers of antibiotic-resistant bacteria in wastewater compared to the natural environment (Kim and Aga, 2007). Little is currently known about the dynamics of antibiotic-resistant bacteria and genes encoding antibiotic resistance in wastewater treatment plants (WWTPs).…”
Section: Introductionmentioning
confidence: 99%
“…ARGs have been detected at all stages of the municipal wastewater treatment process (Lachmayr et al, 2009;Munir et al, 2011), and the vast majority of ARGs are discharged from the municipal wastewater treatment process together with sewage sludge (Bondarczuk et al, 2016). Land application is one of the key management approaches of sewage sludge from wastewater treatment plants (Kim and Aga, 2007). This practice is cost effective with added benefits from its residual nutrients (Candela et al, 2007), but it also represents a major pathway of ARGs spread onto farmlands (Chen and Zhang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various studies have demonstrated that wastewater and animal waste contain large numbers of resistant bacteria, which can pass through the wastewater treatment plant (WWTP) and reach the receiving water bodies (Teuber, 2001;Kü mmerer, 2004;Jury et al, 2011;Rizzo et al, 2013;Zurfluh et al, 2013). There is growing concern that continuous discharge of these contaminants may, at least locally, lead to an increase in the natural resistance background levels and thus enhance the likelihood of antibiotic-resistance genes (ARGs) being transferred back to human and animal commensals or even pathogens (Kim and Aga, 2007;Martinez, 2009b;Cantas et al, 2013). In the long term, this 'environmental loop' could contribute to the spread of resistance in pathogens and undermine the effectiveness of current and future antibiotics.…”
Section: Introductionmentioning
confidence: 99%